Work-family conflict and depressive symptoms among working couples: a spillover-crossover process - Nasharudin, Nurfazreen Aina Muhamad; Rui, Zhao (Intelektual Pustaka Media Utama, 2024)
The study aimed to examine the effect of work-family conflict (WFC) and family-work conflict (FWC) on the level of depressive symptoms among working husbands and wives. First, the study proposed that wife’s WFC influences the husband’s level of depressive symptoms via the mediation of the husband’s FWC. Second, the study predicted that the husband’s WFC leads to the wife’s level of depressive symptoms through the mediation of the wife’s FWC. The study utilized a cross-sectional design that involved 330 teachers and their spouses (N=660) as a study sample. The results show wife’s WFC of strain-based leads to the husband’s depressive symptoms via the husband’s FWC of strain-based. WFC behavior-based of the husband influences the degree of the wife’s depression symptoms via the wife’s behavior-based FWC, whereas WFC time-based of the husband causes the wife to experience depressive symptoms through the wife's FWC. The current findings provide crucial knowledge to the literature as they discover the specific aspects of WFC and FWC that affect individuals’ psychological health.